The appropriate role of agricultural insurance in developing countries - Hazell, Peter B. R. (Wiley, 1992)
Multiple‐risk crop insurance programmes have proven expensive to governments but have not lived up to their expectations. Many agricultural risks cannot be insured on a financially sound basis, but there is scope for increased insurance of farm assets, of the life and health of rural people, and of some specific perils that affect crop and livestock yields. Such insurance could be efficiently provided by the private sector if governments were to remove some of the important constraints impinging on commercial insurers. The greatest challenge is to find ways of insuring low‐income rural households against natural hazards on a financially sound basis. Simple lottery schemes that provide insurance against catastrophic weather events (e.g. drought or flood) recorded at regional weather stations might prove effective.